EXPECTED ROLES OF NURSES AND MIDWIVES IN BOTSWANA - Magowe, Mabel Kefilwe; Seboni, N M; Rapinyana, O; Phetogo, K (Africa Journal of Nursing and Midwifery, 2016)
Aim The roles and tasks of nurses and midwives have developed significantly over the years, calling for adjustment to the current local consumer needs and expectations. This qualitative study was conducted to explore the perceived tasks and roles of nurses and midwives. Significance of the study The results of this study will provide guidance for development of a culturally relevant Sub Saharan nursing and midwifery practice model, and curriculum development. Methods The larger descriptive cross sectional qualitative regional study involved 9 Sub-Saharan African countries. We present the Botswana component of this study. Respondents were patients, community leaders, and nurse-leaders, selected through purposive sampling from different settings. The University Of Botswana Office Of Research and Development, and the Ministry of Health Research and Development Committee gave permission for the study. Participants gave written informed consent, completed a 16-item demographic questionnaire, and engaged in focus group discussions about the perceived tasks and roles of nurses and midwives. Qualitative data were textually analysed to generate themes and subthemes, supported by verbatim excerpts. Results Respondents stated that nurses and midwives in Botswana operate at different levels of the health care system, with dependent, interdependent and independent roles. Nurses and midwives were expected to be receptive, patient, respectful, compassionate, and knowledgeable about their work. The perceived roles included caring, collaboration, advocacy, leadership, supervision, mentoring, management and other expanded roles. Discussion/Conclusion/recommendations Participants highlighted the expanded roles that nurses and midwives performed beyond their scopes of practice and education, hence the need for regulation, training and incentives. Â  Â 